2013
DOI: 10.1371/journal.pone.0080004
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Tissue Engineering In Vivo: A Comparative Study Using Layered Silk Fibroin Scaffolds from Mulberry and Nonmulberry Silkworms

Abstract: The ability to treat osteochondral defects is a major clinical need. Existing polymer systems cannot address the simultaneous requirements of regenerating bone and cartilage tissues together. The challenge still lies on how to improve the integration of newly formed tissue with the surrounding tissues and the cartilage-bone interface. This study investigated the potential use of different silk fibroin scaffolds: mulberry (Bombyx mori) and non-mulberry (Antheraea mylitta) for osteochondral regeneration in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…The inherent integrin binding tri-peptide sequence (Arg-GlyAsp) of A. mylitta fibroin [9] serves to augment cellular interactions due to better cell attachment, and thus aid bone regeneration. Earlier studies have shown that both 2D and 3D matrices of fibroin from A. mylitta promote osteogenic differentiation of human MSCs [ 22], while our previous investigations yielded that scaffolds fabricated using 2 wt% non-mulberry NSF are a better choice for cell proliferation [23].Due to only a limited number of in vivo studies having been performed with SF from Antheraea mylitta [14,15], the possibility of translating nanofibrous NSF scaffolds to clinical trial phase remains an uphill task.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The inherent integrin binding tri-peptide sequence (Arg-GlyAsp) of A. mylitta fibroin [9] serves to augment cellular interactions due to better cell attachment, and thus aid bone regeneration. Earlier studies have shown that both 2D and 3D matrices of fibroin from A. mylitta promote osteogenic differentiation of human MSCs [ 22], while our previous investigations yielded that scaffolds fabricated using 2 wt% non-mulberry NSF are a better choice for cell proliferation [23].Due to only a limited number of in vivo studies having been performed with SF from Antheraea mylitta [14,15], the possibility of translating nanofibrous NSF scaffolds to clinical trial phase remains an uphill task.…”
Section: Discussionmentioning
confidence: 93%
“…PCL itself is reasonably biocompatible and biodegradable, supports a wide range of cells [20], and can be conveniently electrospun into nanofibrous matrices. Silk, as a raw material for tissue engineering, has abundant availability, is FDA approved for repair of tendons and ligaments, can serve as a regenerative template for several tissues, and is commercially marketed for biomedical applications [14]. Such aspects are not observed for most other biomaterials in contention for tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total amount of growth factors loaded onto the scaffolds was 1 µg BMP-2 and 5 ng TGF-β3. 28 Intraperitoneally injected mixture of ketamine HCl (80 mg/Kg) and xylazine (10 mg/Kg) served as an anesthetic for animals. OCD (1 mm diameter ×3 mm depth) were created in the patellar groove of the knee joints using both a hand drill and a dental burr (Figure S1B-G).…”
Section: In Vivo Biocompatibilitymentioning
confidence: 99%